Physcial and mental health problems of the elderly in nursing homes in Kuantan, Pahang - Md Aris, Mohd Aznan; Draman, Samsul (Faculty of Medicine, International Islamic University Malaysia, 2007)
Aim of study: To describe the residents of nursing home for the elderly in relation to their socio-demographic, physical and mental profiles. Method: A cross-sectional study design was carried out. The elderly in two selected nursing homes in Kuantan, Pahang were interviewed. The respondents were interviewed using a structured questionnaire which included the biodata, social background, medical illness, presence of cognition, depression and ability to perform basic activities of daily living (ADL). Results: Results are available for 36 respondents out of 41 residents, giving a response rate of 87.8%. Chinese (77.8%), male (63.9%), single or divorced (50%), and low income (69.4%) was consisted the majority. Most respondents (86.1%) suffered from chronic illness, 61.1% were functional dependent (according to Barthel index), 33.3% have cognitive impairment (according ECAQ) and 22.2% have depression (according to GDS-14). The most common functional dependence was mobility on level surface (47.2%), followed by climbing stairs (38.9%). Conclusion: This study had identified chronic illness, cognitive impairment, depression, and functional decline as major health problems of the elderly in nursing homes that require greater attention and intervention.